China and the Future International Order(s). Issue 1 (7th March 2018) - Tang, Shiping
Abstract: In this essay I survey the key themes within China's discourse on international order, especially how China views its position and role in shaping the existing and future order. I go on to explore the possible implications of China's thinking and actions toward the existing international order. I conclude that overall, China sees no need for and hence does not seek fundamental transformation, but rather piecemeal modification of the existing order. In fact, China has been quite content with the existing order that supports globalization, despite occasional rhetoric indicating otherwise. In the near future, China will likely invest heavily in two key issue areas: (1) regionalism in East Asia and Central Asia; and (2) interregional cooperation and coordination. Perhaps unsurprisingly, China's ambitious "One Belt and One Road" initiative seeks to integrate these two issue areas.